Kebijakan Manajemen Saat Pandemi dan Pasca Pandemi, Desa Wisata Kampung Labirin Bogor Tengah - Nugraha, Rizki Nurul; Putra, Eka Syah; Salsabila, Raden Ajeng Dhea Ayu; Wittsdy AS, Joy H endrikh (Peneliti.net, 2023)
The tourism village sector is still a mainstay in driving the revival of the post-pandemic village economy. The importance of holding village-based tourism activities aims to improve the socio-economic conditions of the related village communities. Apart from being built from CSR Astra, Kampung Labirin is also working with the Terminal Rain Foundation to develop the 3-hectare village into a tourist village. This study aims to analyze the management policies implemented during the COVID-19 pandemic and post-pandemic in Kampung Labirin Tourism Village. This village is one of the famous tourist destinations for its jungle maze, which attracted many tourists before the pandemic. However, the COVID-19 pandemic caused a significant reduction in tourist arrivals and had a negative impact on the local economy. The results of this study indicate that Kampung Labirin Tourism Village has implemented various management policies during the CoVID-19 pandemic to investigate its impact. These policies include reducing visit capacity, implementing strict health protocols, developing digital tourism products, and collaborating with related parties to promote safety and hygiene